PEMBERDAYAAN EKONOMI MASYARAKAT DESA MELALUI PELATIHAN PEMBUATAN NUGGET BERBAHAN BAKU DAGING ITIK - SUTARPA, I N S. (Buletin Udayana Mengabdi, 2012)
ABSTRACT This community services took place in the Village of Babahan-Tabanan regency involving 21 participants. It was carried out at Balai Desa Babahan on 26th July 2008. This socialization aimed to demonstration of duck meat restructured be duck nugget. The result of activity on the whole succes. The participant very enthusiastic and happiness with duck nugget. It can be concluded that, develop of society economic Babahan Village with giving of exercise production of duck nugget very relevant with wish society.